Corporate Turnarounds in the High-tech Industry in UK - Xiao, Haixia (2009)
Prior research on corporate turnaround relates to those organizations that have managed to move from poor performance to high performance within a relatively short time period by a case-study approach. The study also explores the role of leadership as a key factor in making turnaround successful as characterized by the change in CEO and in the board of directors. Finally, it explores the incentive systems of those firms during the turnaround.